2021
DOI: 10.1080/21655979.2021.1937906
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers and immune cell infiltration in acute myocardial infarction (AMI) using bioinformatics strategy

Abstract: Acute myocardial infarction (AMI) was considered a fatal disease resulting in high morbidity and mortality; platelet activation or aggregation plays a critical role in participating in the pathogenesis of AMI. The current study aimed to reveal the underlying mechanisms of platelets in the confrontation of AMI and potential biomarkers that separate AMI from other cardiovascular diseases and healthy people with bioinformatic strategies. Immunity analysis revealed that the neutrophil was significantly decreased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…In this study, it was shown that calcitriol can reduce the expression of the key gene FCGR3A. Previous studies (30)(31)(32) have shown that calcitriol can reduce the expression level of RAGE in cardiomyocytes, reduce the accumulation of AGE in the aortic wall of diabetic rats, reduce the expression level of AGE-induced interleukin 6 (IL-6), and inhibit the activity of NF-κB.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, it was shown that calcitriol can reduce the expression of the key gene FCGR3A. Previous studies (30)(31)(32) have shown that calcitriol can reduce the expression level of RAGE in cardiomyocytes, reduce the accumulation of AGE in the aortic wall of diabetic rats, reduce the expression level of AGE-induced interleukin 6 (IL-6), and inhibit the activity of NF-κB.…”
Section: Discussionmentioning
confidence: 69%
“…Nevertheless, there is a lack of agreement on the optimal cardiac biomarkers. The immune response plays an essential role in the development and repair of AMI [13]., and macrophages, as an important component of intrinsic immunity, can be divided into pro-in ammatory M1-type macrophages and anti-in ammatory M2-type macrophages [14]. Different subtypes of macrophages are capable of performing essential functions in tissue repair after AMI, including phagocytosis of necrotic tissue cell debris, regulation of angiogenesis, and in uence on brosis and scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…They found that Aqp1, Armcx1, Gsta4, Hist3 h2 a, and Il17 as hub genes of STEMI were mainly enriched in cell membrane signal transduction, while Olr1, Nap1 l3, Gfer, Dohh, Crispld1, and Ccdc8 b as hub genes of NSTEMI were markedly related to energy metabolism [36]. Intriguingly, Xie et al inferred that four genes (FN1, CD34, LPL, and WWTR1) were capable of distinguishing STEMI patients from healthy controls and SCAD [37]. Wang et al identified 4 hub genes (LILRB2, TLR2, NCF2, and S100 A9) related to AMI based on three databases (GSE, GSE, and GSE) [38].…”
Section: Discussionmentioning
confidence: 99%